Recent advances in understanding thermomorphogenesis signaling. (August 2022) - Delker, Carolin; Quint, Marcel; Wigge, Philip A.
Abstract: Plants show remarkable phenotypic plasticity and are able to adjust their morphology and development to diverse environmental stimuli. Morphological acclimation responses to elevated ambient temperatures are collectively termed thermomorphogenesis. In Arabidopsis thaliana, morphological changes are coordinated to a large extent by the transcription factor PHYTOCHROME-INTERACTING FACTOR 4 (PIF4), which in turn is regulated by several thermosensing mechanisms and modulators. Here, we review recent advances in the identification of factors that regulate thermomorphogenesis of Arabidopsis seedlings by affecting PIF4 expression and PIF4 activity. We summarize newly identified thermosensing mechanisms and highlight work on the emerging topic of organ- and tissue-specificity in the regulation of thermomorphogenesis.